2019
DOI: 10.1007/s10608-019-10049-4
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Trait Mindfulness and Self-compassion with Obsessive-Compulsive Disorder Symptoms: Results from a Large Survey with Treatment-Seeking Adults

Abstract: Little is known about the role of mindfulness and self-compassion in obsessive-compulsive disorder. This cross-sectional study examined associations of mindfulness and self-compassion with obsessive-compulsive disorder symptoms and with the obsessive beliefs and low distress tolerance thought to maintain them. Samples of treatment-seeking adults (N = 1871) and non-treatment-seeking adults (N = 540) completed mindfulness, self-compassion, obsessive-compulsive disorder, anxiety, depression, obsessive beliefs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 95 publications
5
12
1
Order By: Relevance
“…This finding supports the idea that emotion regulation deficits may play a relevant role for patients with OCD. Unlike the recently published study by Leeuwerik et al (2019), self‐compassion did not emerge as a significant predictor. The mediation analysis provides one explanation for this result as the self‐compassion–symptom severity relationship was found to be mediated by emotion regulation difficulties.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding supports the idea that emotion regulation deficits may play a relevant role for patients with OCD. Unlike the recently published study by Leeuwerik et al (2019), self‐compassion did not emerge as a significant predictor. The mediation analysis provides one explanation for this result as the self‐compassion–symptom severity relationship was found to be mediated by emotion regulation difficulties.…”
Section: Discussioncontrasting
confidence: 99%
“…The hypotheses were largely supported by the data. As anticipated and in accordance with prior research (Berman et al, 2018;Fergus & Bardeen, 2014;Fernández de la Cruz et al, 2013;Leeuwerik et al, 2019;Wetterneck et al, 2013;Yap et al, 2018), symptom severity and obsessive beliefs were negatively correlated with self-compassion and positively associated with emotion regulation difficulties. In line with our expectation and previous studies (Finlay-Jones et al, 2015;Scoglio et al, 2018;Vettese et al, 2011), a strong and negative correlation between selfcompassion and difficulties in emotion regulation existed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Two recent studies on OCD patients demonstrated that self-compassion was correlated to reduced OCD symptoms and that this correlation was partially explained by lower emotion regulation difficulties ( Chase et al, 2019 ; Eichholz et al, 2020 ). Another recent cross-sectional study comparing treatment-seeking adults ( N = 1871) and non-treatment-seeking adults ( N = 540) found that participants with clinically significant OCD symptoms reported lower trait mindfulness and self-compassion compared to participants with clinically significant anxiety/depression and to non-clinical controls, with mindfulness and self-compassion as unique predictors of OCD symptoms, even when controlling for depression severity ( Leeuwerik et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%